2010
DOI: 10.4111/kju.2010.51.12.819
|View full text |Cite
|
Sign up to set email alerts
|

Is a Decreased Serum Testosterone Level a Risk Factor for Prostate Cancer? A Cohort Study of Korean Men

Abstract: PurposeTo investigate patients who had transrectal ultrasonography (TRUS)-guided prostate biopsy to define the role of the serum testosterone level in predicting prostate cancer risk and its association with a high Gleason score.Materials and MethodsA total of 568 patients who underwent prostate biopsy were entered in this study. We divided the patients into two groups according to serum testosterone level (median level, 3.85 ng/ml): the high-testosterone group (n=285) and the low-testosterone group (n=283). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
2
34
0
2
Order By: Relevance
“…10,11 However, an independent association has not been uniformly demonstrated in all investigations. 12,13 Most studies have been performed in Caucasian and Asian populations, yet without specifying the effect of demographic characteristics on the association between TT and higher-grade PCa. Possible explanations for the inconsistency between existing studies include demographic variability, variable cutoffs for hypogonadism and biased samples.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, an independent association has not been uniformly demonstrated in all investigations. 12,13 Most studies have been performed in Caucasian and Asian populations, yet without specifying the effect of demographic characteristics on the association between TT and higher-grade PCa. Possible explanations for the inconsistency between existing studies include demographic variability, variable cutoffs for hypogonadism and biased samples.…”
Section: Introductionmentioning
confidence: 99%
“…Rather paradoxically, considerable studies targeting the biopsy or prostatectomy population reported that low testosterone levels were associated with the overall prostate cancer risk or high-grade prostate cancer risk. Moreover, some studies have reported that a low testosterone level is associated with unfavourable pathological findings in specimens and the biochemical recurrence rate after radical prostatectomy [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have reported that a low level of testosterone is associated with increased detection of prostate cancer at biopsy, pathologically advanced prostate cancer, and a worse prognosis [12][13][14][15][16][17][18][19]. However, only a few results have been reported in the field of prostate biopsy, and they have not provided consistent conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of even greater concern, neither prostate specific antigen (PSA), prostate volume, nor cancer progression has been found to increase with increasing testosterone levels in men with untreated prostate cancer (Morgentaler et al, 2011). Interestingly, evidence is even emerging to show that patients with a lower serum testosterone level may have a higher risk of prostate cancer than patients with high serum testosterone (Shin et al, 2010). Recent scrutiny of the seminal work conducted by Huggins and Hodges has revealed some fundamental flaws and methodological failings (Morgentaler, 2006).…”
Section: Prostate Cancermentioning
confidence: 99%